The Antibacterial Activity Test Comparison of Green and Black Tea Ethanol Extract (Camellia sinensis) Against Propionibacterium acnes - Aliyah Fahmi; Sumaryati Syukur; Zulkarnain Chaidir; Sri Melia (Science Midwifery, 2022)
A study was conducted in connection with the comparison of antibacterial activity tests between ethanol extracts from green tea leaves and black tea leaves (Camellia sinensis) against Propionibacterium acnes. There were obtained by a softening technique that was softened for 24 hours. The filtrate was then concentrated to give a concentrated extract and evaporated ethanol content. The concentrated extract was then diluted with distilled water to extract 5%, 10%, and 15% concentration variations. The test method for inhibitory activity was the disc method using distilled water as a negative blank. The results obtained with blank, 5%, 10% and 15% green tea were 0. 5.25; 7.05 and 7.95 mm and black tea ethanol extract were 0; 2.50; 3.20 and 5.30 mm. The conclusion of this study is that the concentration of the extract is directly proportional to its inhibitory power, and the green tea ethanol extract is more potent than the black tea ethanol extract, so both can be used as antibacterial agents against P. acnes.